Commensal Clostridiales strains mediate effective anti-cancer immune response against solid tumors - Montalban-Arques, Ana; Katkeviciute, Egle; Busenhart, Philipp; Bircher, Anna; Wirbel, Jakob; Zeller, Georg; Morsy, Yasser; Borsig, Lubor; Glaus Garzon, Jesus F.; Müller, Anne; Arnold, Isabelle C.; Artola-Boran, Mariela; et al. (Cell host & microbe, 2021)
Despite overall success, T cell checkpoint inhibitors for cancer treatment are still only efficient in a minority of patients. Recently, intestinal microbiota was found to critically modulate anti-cancer immunity and therapy response. Here, we identify Clostridiales members of the gut microbiota associated with a lower tumor burden in mouse models of colorectal cancer (CRC). Interestingly, these commensal species are also significantly reduced in CRC patients compared with healthy controls. Oral application of a mix of four Clostridiales strains (CC4) in mice prevented and even successfully treated CRC as stand-alone therapy. This effect depended on intratumoral infiltration and activation of CD8+ T cells. Single application of Roseburia intestinalis or Anaerostipes caccae was even more effective than CC4. In a direct comparison, the CC4 mix supplementation outperformed anti-PD-1 therapy in mouse models of CRC and melanoma. Our findings provide a strong preclinical foundation for exploring gut bacteria as novel stand-alone therapy against solid tumors. [Display omitted] •Clostridiales bacteria are associated with low tumor burden in colon cancer models•Selected Clostridiales bacteria are diminished in colorectal cancer patients•A mix of Clostridiales strains have a potent anti-tumor effect via CD8+ T cells•Clostridiales treatment is effective in solid tumors independently of anti-PD-1 Montalban-Arques et al. report that Clostridiales bacteria strains that are significantly reduced in colorectal cancer patients compared with healthy individuals are effective in driving a potent anti-tumor response in solid tumors. They demonstrate that this is via activation of CD8+ T cells, independently of anti-PD-1 immunotherapy.